Penerapan 5 Aspek Kunci Untuk Memenuhi Standart E-Fullfilment Pada Perusahaan: Studi Kasus Online Store Akai Print Perbaungan - Hafizh Wahyu Wijaya Marpaung; Afrillia Afrillia; Aprillina Putri; Cut Dila Sari ; Nurbaiti Nurbaiti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This scientific article discusses the implementation of 5 key aspects to meet e-fullfillment standards in a company. Consumer Management, Catalog Management, Order Management, Delivery Management, and Inventory Management. These five things are key processes to meet the